2022
DOI: 10.3389/fpsyt.2022.925012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of molecular signatures associated with sleep disorder and Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) and sleep disorders are both neurodegenerative conditions characterized by impaired or absent sleep. However, potential common pathogenetic mechanisms of these diseases are not well characterized.MethodsDifferentially expressed genes (DEGs) were identified using publicly available human gene expression profiles GSE5281 for AD and GSE40562 for sleep disorder. DEGs common to the two datasets were used for enrichment analysis, and we performed multi-scale embedded gene co-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…DCs play specific roles in the immune microenvironment during processes such as aging and in AD ( Mrdjen et al, 2018 ). pDCs showed markedly extensive infiltration in AD ( Liang et al, 2022 ). Furthermore, naive B cells and M2 macrophages found a high infiltrated degree in patients with AD when we used the CIBERSORT method.…”
Section: Discussionmentioning
confidence: 99%
“…DCs play specific roles in the immune microenvironment during processes such as aging and in AD ( Mrdjen et al, 2018 ). pDCs showed markedly extensive infiltration in AD ( Liang et al, 2022 ). Furthermore, naive B cells and M2 macrophages found a high infiltrated degree in patients with AD when we used the CIBERSORT method.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, while no studies directly related to ALS were discovered, other studies related to other neurological diseases were found in the cases of the EEF1A1 [ 49 ], COX5A [ 50 ] and RPL12 and RPL15 genes [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the past literature, there is the identification of AD-related hub genes by using only the modular genes in DEGs or WGCNA to identify AD hub genes, which is still slightly insufficient in terms of in data selection and processing ( Wu et al, 2021 ; Liang et al, 2022 ). In comparison, the strengths in our study: 1.…”
Section: Discussionmentioning
confidence: 99%